Is the Albanian's religion really "Albanianism"? religion and nation according to Muslim and Christian leaders in Albania - Endresen, Cecilie (Albanische Forschungen (Otto Harrassowitz (Firm), 2012)
For over a century, Albanians have been urged to view religious differences as unimportant. But are they? By conducting an unique set of interviews with representatives of the country's high-ranking clerics, Cecilie Endresen tries to answer this question. The clerics speak of an interplay between nation and religion in the their own symbolic universes and expound on such themes as salvation, religious tolerance, historical developments, theological differences, and politics